Enhancing Culture and Retention through an Expanded Leader-Member Exchange Theory: A Focus on Commitment and Fairness - Willie, Michael Mncedisi (Manunggal Halim Jaya, 2025)
This study investigates the implications of the high-quality Leader-Member Exchange (LMX) model on the dynamics of leader-follower relationships. It critically examines the model's limitations in addressing behavior, fairness, and mutual responsibilities within changing organizational contexts. A thorough literature review was conducted to analyze the relationship between LMX theory and its effects on key organizational outcomes, such as employee commitment, retention, and organizational culture. The result of this study states that the enhanced high-quality Leader-Member Exchange (LMX) model emphasizes the critical role of reciprocal obligations between leaders and employees in fostering affective, continuance, and normative commitment—key factors for improving employee retention. It also underscores the importance of cultivating an organizational culture that aligns with employee values, enhancing job satisfaction and reducing turnover. Strengthened high-quality LMX relationships ultimately contribute to sustainable organizational success. Practical Implications of this study state that organizations and scholars can apply the proposed model to improve leadership practices by fostering equitable, supportive, and robust LMX interactions. Addressing potential inequities and promoting inclusivity within the workplace can further enhance employee retention and satisfaction. This study advances the existing body of knowledge by introducing a conceptual model derived from literature. It demonstrates how mutual respect, friendships, and reciprocal responsibilities are precursors to employee commitment. The findings provide actionable insights for practitioners and policymakers to foster positive leader-member relationships and implement more effective and inclusive organizational structures.